An exploration of the integration of environmental education by Natural Sciences and Technology teachers - Sanele Toys MNGOMEZULU; Lettah SIKHOSANA (Social Sciences and Education Research Review)
This paper investigated how Natural Sciences and Technology teachers integrate environmental education into their teaching. Due to ongoing changes in the South African school curriculum, teachers have struggled to incorporate environmental education effectively. The study used an interpretative research paradigm and a multiple case study design, guided by the theoretical framework of social constructivism. It was conducted in the iLembe district of KwaZulu-Natal province in South Africa and involved three grade 6 primary school teachers specializing in Natural Sciences and Technology. Data collection methods included semi-structured interviews, observations, and document analysis, and the data was analyzed thematically. The findings revealed that some teachers had misconceptions about integrating environmental education. To address this, it is recommended that subject advisors take a more active role in promoting the integration of environmental education during content workshops. The study also found that teachers relied on instructional strategies that hindered effective integration. Therefore, teachers should explore a broader range of instructional strategies. Lastly, the study found that the support provided by departmental officials was insufficient, and it is suggested that they establish connections with other stakeholders to facilitate collaboration and reintroduce environmental education programs in schools.